Psychological socialism : the Labour Party and qualities of mind and character, 1931 to the present. - Nuttall, Jeremy (Labour Movements Critical Studies., 2006)
To Labour?s first Prime Minister, Ramsay MacDonald, socialism meant not only?satisfactory figures of death rates and ... improved houses? but also the?mental cleanliness, the moral robustness of our people.? This book explores the neglected theme of individual character and?mental qualities? in British social democratic thought and Labour Party history. How important was it for the centre-left that citizens be?good people?? What was the relationship between socialism and psychology in the 1930s? Did Labour?s technocratic, statist socialism of the 1950s and 1960s downgrade moral and mental p.